Some Smooth Compactly Supported Tight Framelets - Antolín, A. San; Zalik, R. A. (Communications in Mathematics and Applications, 2012)
For any dilation matrix with integer entries, we construct a family of smooth compactly supported tight wavelet frames in L^2(R^d), d1. Estimates for the degrees of smoothness of these framelets are given. Our construction involves some compactly supported refinable functions, the Oblique Extension Principle and a slight generalization of a theorem of Lai and Stöckler.